Physical Characteristics and Body Image of Japanese Female University Long-Distance Runners - Kagawa M. (2023)
Featured Application: Many Japanese female university long-distance runners misperceive their current weight and adiposity. However, their body dissatisfaction may not be based on their physique or external information sources. Understanding their past experience and its impact on their body image may be beneficial. Further research on the effects of educational programs for the improvement of performance on the correction of body image and behaviour modification may be warranted. While female long-distance runners are considered to have strong body dissatisfaction and body concerns, body-image research that incorporates detailed anthropometric and body composition parameters is still limited. The present study therefore investigates the physical characteristics and body image of Japanese female long-distance runners and explores the factors that influence their body image. Detailed anthropometric and body composition assessment using a dual-frequency bioelectrical impedance analysis (DFBIA) was conducted on 30 Japanese female university long-distance runners. In addition, a questionnaire that included the Body Satisfaction Scale (BSS) and the Ben-Tovim Walker Body Attitudes Questionnaire (BAQ) was administered. On average, the participants had relatively low body mass index (BMI) and percentage body fat (%BF) (BMI: 18.3 ± 1.6 kg/m2; %BF: 19.7 ± 4.4%), but about 50–60% of them perceived themselves as being fat or having an excessive level of %BF. Their BSS scores were not associated with their measured physique. However, the anthropometric variables of the limbs were associated with the BAQ and its subscales. There was no single source that the majority referred to obtain information on their body, and performance was the only reason for their increased body concern. In order to better understand the factors that influence their body dissatisfaction and the effects of providing accurate information on behaviour modification, further investigation is warranted.